2017
DOI: 10.1080/15384047.2017.1312230
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phosphorylated Hippo pathway kinases (MST1/2 and LATS1/2) in HER2-positive and triple-negative breast cancer patients treated with neoadjuvant therapy

Abstract: The Hippo kinases MST1/2 and LATS1/2 inhibit the oncoproteins TAZ/YAP and regulate T cell function. Hippo kinases also cooperate with the ATR-Chk1 and ATM-Chk2 pathways, central orchestrators of the DNA damage response (DDR). We hypothesized that MST1/2 and LATS1/2 localization differently impacts the efficacy of neoadjuvant therapy (NAT) in breast cancer, being protective when expressed in the cytoplasm of tumor cells and in tumor-infiltrating lymphocytes, whereas representing molecular determinants of chemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Caspase-dependent cleavage or phosphorylation of its activation loop lead to MST1 translocation to the nucleus, which may be important for its pro-apoptotic functions [32]. MST1 activity can be affected by different molecular events, including a dysregulated crosstalk with oncogenic pathways and altered post-translational modifications at the protein level [10,[33][34][35]. In our study, the immunohistochemical evaluation of MST1 expression confirmed a diminished expression in GBC compared with CC.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Caspase-dependent cleavage or phosphorylation of its activation loop lead to MST1 translocation to the nucleus, which may be important for its pro-apoptotic functions [32]. MST1 activity can be affected by different molecular events, including a dysregulated crosstalk with oncogenic pathways and altered post-translational modifications at the protein level [10,[33][34][35]. In our study, the immunohistochemical evaluation of MST1 expression confirmed a diminished expression in GBC compared with CC.…”
Section: Discussionsupporting
confidence: 62%
“…The anticancer effects of MST1 have been reported for numerous types of cancer, including colorectal [34,35], breast [10,36,37] and lung cancers [38]. It should be noted that cytoplasmic expression of MST1 in cancer cells has been related with its function as a protective molecule acting in the canonical Hippo signaling pathway, through the inhibition of oncogenic YAP/TAZ [33]. In addition, MST1 can be cleaved by caspases which promotes its nuclear translocation, where it induces chromatin condensation and apoptosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MST1/2 may function as a potential predictive biomarker in HER2-positive and TN breast cancer patients. 71 The expression of TAZ/YAP was associated with inferior survival in male breast cancer patients. 72 The above studies support the notion that TAZ/YAP expression is correlated with tumor metastasis and patient outcomes.…”
Section: Role Of Hippo Pathway Components In Breast Cancer Metastasismentioning
confidence: 99%
“…As previously described, 24 YAP is also only weakly expressed or undetectable in HMCLs. In contrast, upstream regulators of the Hippo pathway, LATS1 and MST1, which are normally suppressed in solid tumors, [30][31][32] were expressed at higher levels in HMCLs compared with the lung cancer cell line A549 ( Figure 1C-D). These results suggest that the role of the Hippo pathway, particularly TAZ, in tumorigenesis is fundamentally different in MM and other hematological malignancies compared with their previously established oncogenic roles in solid tumors.…”
Section: Expression Of Taz Predicts Survival Outcomes In Patients Witmentioning
confidence: 95%